ANALISIS KOINTEGRASI DAN ERROR CORRECTION MODEL ANTARA INDEKS HARGA SAHAM GABUNGAN DENGAN INDEKS BURSA GLOBAL DAN NILAI TUKAR - , Riyanti Ridzki Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was intended to know and analyze cointegration between Jakarta Composite Index (JCI) with global stock indices (Dow Jones, Hang Seng, FTSE) and exchange rates (US Dollar, Hong Kong Dollar, Euro) through cointegration and error correction model. The results showed that in the short term there is a significant correlation between the Dow Jones Index, Hang Seng Index, FTSE and Euro. Pattern JCI relationship with Dow Jones Index, FTSE and Euro is positive, while the Hang Seng Index is negative. Meanwhile, in the long run there is a significant correlation between the Dow Jones Index, Hong Kong Dollar and U.S. Dollar. The pattern of relationships Dow Jones Index and Hong Kong dollar is positive, while the U.S. dollar is negative in the long run.